Loss of cell‐extracellular matrix interaction triggers retinal regeneration accompanied by Rax and Pax6 Activation. Issue 6 (25th February 2013) - Nabeshima, Ayaka; Nishibayashi, Chisato; Ueda, Yoko; Ogino, Hajime; Araki, Masasuke
Summary The whole retina regenerates from retinal pigmented epithelial (RPE) cells by transdifferentiation in the adult newt and Xenopus laevis when it is surgically removed. We produced a transgenic animal line, in which EGFP expression is under the control of Rax pomotor. Using F1 and F2 generations, we analyzed Rax‐EGFP expression during retinal regeneration in a tissue culture model. In the culture, 4 zones were distinguished as RPE cells migrating outwards from the periphery of the explant: the explant zone, epithelial zone, transition zone and differentiation zone. Expression of transcription factors such as Pax6 and Rax‐EGFP was observed in different zones. Rax‐EGFP expression preceded Pax6 expression, and the expression of both genes occurred in RPE cells that had lost contact with the basement membrane facing the choroid. We have developed a new culture method in which RPE tissues are embedded in Matrigel. This method has many advantages over the previous gel‐overlay method to reproduce construction of 3D‐retinal structures and clearly showed that RPE cells need to be detached from the choroid before entering the regeneration pathway. The present results indicate that the temporal changes in cell‐cell and cell‐extracellular matrix interactions regulate transdifferentiation. genesis 51:410–419. © 2013 Wiley Periodicals, Inc.